2021
DOI: 10.1186/s12909-021-02665-0
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors associated with physician trainee concern over missed educational opportunities during the COVID-19 pandemic

Abstract: Background The COVID-19 pandemic resulted in a transformation of clinical care practices to protect both patients and providers. These changes led to a decrease in patient volume, impacting physician trainee education due to lost clinical and didactic opportunities. We measured the prevalence of trainee concern over missed educational opportunities and investigated the risk factors leading to such concerns. Methods All residents and fellows at a la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 44 publications
3
14
0
Order By: Relevance
“…Due to the reduction in elective activities and the redeployment, residents reported a decrease in educational activities, with a detrimental effect on their training [ 10 , 11 ]. A survey in a large academic medical centre found that pathology residents were more likely to be concerned about missing educational opportunities compared to other specialties [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Due to the reduction in elective activities and the redeployment, residents reported a decrease in educational activities, with a detrimental effect on their training [ 10 , 11 ]. A survey in a large academic medical centre found that pathology residents were more likely to be concerned about missing educational opportunities compared to other specialties [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…This study has identified a range of general and pandemic-specific stressors experienced by UK trainee doctors working and has explored the association of these stressors with burnout. Previous studies have focused on burnout in healthcare workers during the covid-19 pandemic [ 6 , 7 ]; however, this is one of the very few studies that have focused specifically on doctors in training [ 18 , 19 ]. While exploration of stressors in trainee doctors has been limited [ 18 , 19 ], our study has included a comprehensive range of stressors identified in UK trainee doctors and the previous literature [ 2 , 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some radiology residents felt that their radiology department and their education changed due to the COVID-19 pandemic, 10 potentially more so than their medical and surgical resident colleagues. 46 Despite undergoing changes, program directors and residents felt that learning standards were being adequately addressed for knowledge and interpretation, but case volumes and technical skills were lacking. 9 , 47 Some institutions reported that residents felt their education was negatively impacted by the circumstances of the pandemic, 35 but similar levels of competence 9 appeared to be displayed.…”
Section: Psychosocial Impact and Resident Perception On Disruption To Trainingmentioning
confidence: 99%